VEGF Over-Expression by Engineered BMSC Accelerates Functional Perfusion, Improving Tissue Density and In-Growth in Clinical-Size Osteogenic Grafts - Largo, Rene’ D.; Burger, Maximilian G.; Harschnitz, Oliver; Waschkies, Conny F.; Grosso, Andrea; Scotti, Celeste; Kaempfen, Alexandre; Gueven, Sinan; Jundt, Gernot; Scherberich, Arnaud; Schaefer, Dirk J.; Banfi, Andrea; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
The first choice for reconstruction of clinical-size bone defects consists of autologous bone flaps, which often lack the required mechanical strength and cause significant donor-site morbidity. We have previously developed biological substitutes in a rabbit model by combining bone tissue engineering and flap pre-fabrication. However, spontaneous vascularization was insufficient to ensure progenitor survival in the core of the constructs. Here, we hypothesized that increased angiogenic stimulation within constructs by exogenous VEGF can significantly accelerate early vascularization and tissue in-growth. Bone marrow stromal cells from NZW rabbits (rBMSC) were transduced with a retroviral vector to express rabbit VEGF linked to a truncated version of rabbit CD4 as a cell-surface marker. Autologous cells were seeded in clinical-size 5.5 cm3 HA scaffolds wrapped in a panniculus carnosus flap to provide an ample vascular supply, and implanted ectopically. Constructs seeded with VEGF-expressing rBMSC showed significantly increased progenitor survivival, depth of tissue ingrowth and amount of mineralized tissue. Contrast-enhanced MRI after 1 week in vivo showed significantly improved tissue perfusion in the inner layer of the grafts compared to controls. Interestingly, grafts containing VEGF-expressing rBMSC displayed a hierarchically organized functional vascular tree, composed of dense capillary networks in the inner layers connected to large-caliber feeding vessels entering the constructs at the periphery. These data constitute proof of principle that providing sustained VEGF signaling, independently of cells experiencing hypoxia, is effective to drive rapid vascularization and increase early perfusion in clinical-size osteogenic grafts, leading to improved tissue formation deeper in the constructs.